Lactobacillus cypricasei sp. nov., isolated from halloumi cheese - Lawson, Paul; Wacher, Carmen; Papademas, Photis (My University, 2001)
Four strains of a hitherto unknown bacterium isolated from Halloumi cheese were compared by using phenotypic and phylogenetic studies. Comparative 16S rRNA gene sequencing demonstrated that the strains were identical to each other and represent a new subline within the genus Lactobacillus. The unknown bacterium was readily distinguished from other described Gram-positive catalase-negative taxa by means of biochemical tests and electrophoretic analysis of whole-cell proteins. On the basis of phylogenetic and phenotypic evidence, it is proposed that the unknown bacterium be classified as Lactobacillus cypricasei sp. nov. The type strain of L. cypricasei is CCUG 42961T ( = CIP 106393T)
Keywords: Cheese; Phylogeny; RNA; Electrophoresis; Lactobacillus; Phenotype; DNA; Bacteria